Yassassin - Adolfsson, Gustaf (My University, 2023)
The assignment was enabling of a city part. An urban densification is requested. But architecture is about enabling life. If I only enable buildings this project fails. I’ve seen the lot is an urban planning junk space. But I’ve also seen it utilised, as a buffer. For sports, play, and life. Heard and experienced it. It wouldn’t be sound to evade this fact. It wouldn’t be architectural. Architecture may ignore and impose. It should provoke and evoke. But know why so. Then architecture makes sense. Then it can be more than backdrop or storage. Then it can enable. This is the central hub of this city propposal. It is the essence of Low/Lodger/’Heroes’ All at once All i one.